Peningkatan Kualitas Usaha BUMDes Pujon Kidul dalam Mengembangkan Desa Wisata Tangguh di Masa Pandemik - Luqman Dzul Hilmi; Vina Salviana Darvina Soedarwo; Sri Hartiningsih (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2021)
The Pujon Kidul Regency Government seeks to improve the Tourism Village Business in business units in the pandemic era by implementing health protocol standards and internet technology. The protocols are applied to tourist service units by coaching human resources in improving the service quality. The standard of tourist service facilities was adjusted to support the quality and attract tourists who want security and safety. Both of these matters directly affect the financial reporting activities. So, the procedure is also evaluated to be effective and systematic. There is urgency on how the Village Government can run Village Tourism business units to build the standard health protocols. The program aims to help the Village's Business of Pujon Kidul Tourism Village towards the employees from local citizens in the quality and suitability of services, good facilities, and internet-based financial reporting. Another goal is to support the Strategic Plan for Government policies regarding the formation of Tough Village in the pandemic and become the pilot for other villages. This program uses mentoring and coaching the village partners, which is participatory and has a Bottom-Up model (condition of the partners-decisions problem solving). The final benefit of mentoring is applying technology for internet-based financial management, creating the guidebook for Tough Tourism Village Services in Pujon Kidul, and standardization of facilities and services for the Tourism Village.